2018
DOI: 10.1115/1.4041045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Longitudinal Variation of Vocal Fold Inner Layer Thickness on Fluid-Structure Interaction During Voice Production

Abstract: A three-dimensional fluid-structure interaction computational model was used to investigate the effect of the longitudinal variation of vocal fold inner layer thickness on voice production. The computational model coupled a finite element method based continuum vocal fold model and a Navier-Stokes equation based incompressible flow model. Four vocal fold models, one with constant layer thickness and the others with different degrees of layer thickness variation in the longitudinal direction, were studied. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Damping was simulated using a Rayleigh damping scheme with coefficients a = 24.1915 and b = 0.000127. The vocal fold tissue was modeled as viscoelastic, transversely isotropic material in the other four studies [67][68][69]. A constant density q = 1043 kg/m 3 , in-plane transversal and longitudinal Poisson ratio (m p = 0.9, m pz = 0) inside the layers is used.…”
Section: Models and Materials Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Damping was simulated using a Rayleigh damping scheme with coefficients a = 24.1915 and b = 0.000127. The vocal fold tissue was modeled as viscoelastic, transversely isotropic material in the other four studies [67][68][69]. A constant density q = 1043 kg/m 3 , in-plane transversal and longitudinal Poisson ratio (m p = 0.9, m pz = 0) inside the layers is used.…”
Section: Models and Materials Propertiesmentioning
confidence: 99%
“…A pressure inlet and outlet condition drive the flow, and a nopenetration and a no-slip condition are applied to the walls. For the acoustics equation in four studies [67][68][69][70], soundhard wall boundary conditions are applied at the tissue walls. A total reflecting boundary condition models the free field radiation.…”
Section: Boundary Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Mathematical models and in vivo experiments have suggested that the voice is affected by changes in thickness of both the cover and body of the vocal fold. 29 The cover-body layer thickness ratio significantly affects flow-tissue interactions influencing both fundamental frequency (F0) and vibration pattern. 30 Increased vocal fold thickness (thick TVFM) was believed to result in greater vertical phase difference and longer glottal closure time, leading to stronger harmonic structures.…”
Section: Introductionmentioning
confidence: 99%